Father's Involvement in Feeding and Stimulating Children's Growth and Development with the Incidence of Stunting - Rahma, Valenty Rafaustine; Sari, Citra Windani Mambang; Hendrawati, Sri (Indonesian Journal of Global Health Research, 2024)
Stunting is still the biggest nutritional problem from national to international scope. Indonesia is still closely related to patriarchal culture, although the parenting process requires the active involvement of fathers and mothers in caring for stunted children. The purpose of this study was. Objective to analyze the relationship between father's involvement in feeding and stimulation of child growth and growt and development with the incidence of stunting. This study used a cross-sectional correlational quantitative method with purposive sampling. The sample size was 79 people. Data were collected using the ECLS-B father self-administered questionnaire, which was adapted and modified with the results of the validity test declared valid because it was more than r table (r = 0.444) and the results of the reliability test declared reliable with Cronbach Alpha of 0.852 and 0.741. Data analysis was performed using the Chi-Square test. The results showed no association between father's involvement in child feeding and stimulation of child growth and development with the incidence of stunting (p value=0.888 OR= 0,685; RR=1,128 and p value=0,435; OR=1,071; RR=1,048). This shows that there are other, more dominant factors that influence the incidence of stunting. These factors include inadequate dietary intake, economic constraints, and child feeding errors. Further interventions are needed to increase fathers' involvement in feeding and growth stimulation of stunted children, although there is no direct relationship.